The “Courtesy” (Comitas) of king Vononès - Manaseryan, Ruben («Քոփի Փրինթ» տպագրատուն)
The Parthian king Vononès (8-12), being full of benevolence and courtesy towards his subjects, was however driven out by his nobility. This fact was the consequence of the opposites of thepolitical mentality of the Roman and Parthian societies. Vononès, who returned to the Parthian throne after a long stay as a hostage in Rome, tried to transfer the way of leadership of republican Rome to a tribal society based on the principles of collectivism and personal leveling. In the ideas of the Parthians, the king (vir magnus - Just XLI,6.1) is the embodiment of physical masculinity and exercises power by means of readiness for violence, threats and, accordingly, stimulating fear in his subjects. The fear of the monarch is an incentive to implement his will. The “courtesy” (comitas) of Vononès, which Tacitus speaks of, being a characteristic feature of the political communication in republican Rome, was introduced by him into relations with the subjects. It denied the traditional principles of exercising power by the Arsacids on interpersonal level, and destroyed traditional ideas about the king-lord. We could presume that Vononès practically abolished fear as a means of exercising supreme power. Emperor Claudius, who pursued a policy of terror against the Senate and equites, urged the pretender to the Parthian throne the prince Meherdat to follow the official ideological setting of the principate - an ideal relationship between the ruler (rector) and citizens and not rule as a despot of slaves. These words to Meherdat expose a calculation that the pursuit of these political precepts will only lead to further unrest within the Parthian Empire identical to that which overthrew Vononès. Հռոմից պարթևների հրավերով Արշակունիների գահին բազմած Վոնոնը` Հրահատ IV-ի որդին, յուրացրել էր դեռևս հանրապետական Հռոմում ձևավորված քաղաքական մշակույթը` կառավարման գործելակերպը։ Այն հիմնված էր անձի՝ քաղաքացու իրավունքների հարգման սկզբունքի վրա և իշխանավորից պահանջում էր իր գերակայությունը չշեշտող մոտեցում, արտաքնապես իրա-վահավասար հարաբերությունների պահպանում։ Պրինցիպատի միապետական վարչակարգը որդեգրել էր այդ քաղաքական հանրապետական համակարգը սոսկ ձևապաշտորեն՝ իբրև դաժան բռնաճնշումների վրա հիմնված, իրական իշխանության հարաբերությունների պաշտոնական ծածկույթ։ Կտրված այդ իրողության ըմբռնումից՝ Վոնոնը փորձեց Հռոմի հանրապետական քաղաքական մշակույթը փոխադրել արևելյան ավանդույթապահ հասարակության մեջ, որի պատկերացումներով արքան՝ բռնություն գործածելու միշտ պատրաստակամ տիրակալը, անմիջապես վախ պիտի ներշնչեր իր հպատակներին (metus) որպես իր կամքի կատարման խթան։ Իր հպատակների հետ անմիջական հարաբերությունների մեջ Վոնոնը` հավատարիմ իր քաղաքական պատկերացումներին, ներմուծեց նրբանկատ սիրալիրությունը, նաև անձնական մատչելիությունը։ Դրանով իսկ նա մերժում էր վախը թագավորի հետ հարաբերություններում, փաստորեն քանդում թագավորի մասին կարծրատիպային պատկերացումները։ Նման գործելակերպը ավագանու կողմից մեկնվեց իբրև հռոմեական կայսրից յուրացված ստրկական վարվելակերպի դրսևորում։ Վոնոնը գահընկեց արվեց։ Վոնոնի պատմության մեջ արտացոլվեց Հռոմի և տոհմացեղային քաղաքական մշակույթների իրարամերժությունը, որի հիմքում էին մարդու, անհատի մասին հակադիր պատկերացումները:
Keywords: History